Brown coal char CO2‐gasification kinetics with respect to the char structure part II: Kinetics and correlations. (25th October 2018) - Komarova, Evgeniia; Abosteif, Ziad; Guhl, Stefan; Meyer, Bernd
Abstract: Coal's physical structure is known to affect high‐temperature coal conversion processes such as gasification or combustion. This paper is Part II of the study of brown coal char structural changes during gasification. Firstly, German Lusatian brown coal was gasified in a laboratory‐scale fluidized bed reactor in CO2 within a temperature range of 800–950 °C at atmospheric pressure. Then, physical structure properties were extensively evaluated by means of various techniques. Char specific surface area and its changes during gasification reaction were evaluated using N2 and CO2 physical adsorption techniques. Adsorption isotherms were also interpreted employing unconventional methods in order to obtain the specific surface areas of pores of different sizes. Gasification kinetics were evaluated employing three widely applied kinetic models: the random pore model (RPM), the volume reaction model (VM), and the shrinking core model (SCM). Finally, the instantaneous gasification reaction rate was correlated with the char structural properties at the corresponding conversion degrees. The closest linear correlation appeared between the gasification reaction rate and the specific surface area of mesopores (as determined by N2 adsorption). Furthermore, correlations of the other structural properties with char conversion are provided. Observed structural changes were compared with the assumptions of the kinetic models.